The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s40644-017-0106-8
|View full text |Cite
|
Sign up to set email alerts
|

CT texture analysis: a potential tool for prediction of survival in patients with metastatic clear cell carcinoma treated with sunitinib

Abstract: BackgroundTo assess CT texture based quantitative imaging biomarkers in the prediction of progression free survival (PFS) and overall survival (OS) in patients with clear cell renal cell carcinoma undergoing treatment with Sunitinib.MethodsIn this retrospective study, measurable lesions of 40 patients were selected based on RECIST criteria on standard contrast enhanced CT before and 2 months after treatment with Sunitinib. CT Texture analysis was performed using TexRAD research software (TexRAD Ltd, Cambridge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 17 publications
0
53
0
Order By: Relevance
“…Because chRCC and RO are relatively rare compared to renal clear cell and renal papillary cell carcinoma, radiomic studies of renal tumors are focused on relatively common renal tumors. Studies on the most frequently occurring renal clear cell carcinoma have focused on different aspects such as preoperative diagnosis [19][20][21][22], tumor grade [23], prognostic evaluation [24], and molecular analysis of the cancer genes [25][26][27]. Yu et al [20] extracted the texture features of four types of renal tumors, including renal clear cell carcinoma, renal papillary cell carcinoma, chRCC, and RO.…”
Section: Discussionmentioning
confidence: 99%
“…Because chRCC and RO are relatively rare compared to renal clear cell and renal papillary cell carcinoma, radiomic studies of renal tumors are focused on relatively common renal tumors. Studies on the most frequently occurring renal clear cell carcinoma have focused on different aspects such as preoperative diagnosis [19][20][21][22], tumor grade [23], prognostic evaluation [24], and molecular analysis of the cancer genes [25][26][27]. Yu et al [20] extracted the texture features of four types of renal tumors, including renal clear cell carcinoma, renal papillary cell carcinoma, chRCC, and RO.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that radiomic features may have significant associations with clinical outcomes and gene-expression levels456789. These features can also be used to develop diagnosis or prognosis models that may serve as a tool for personalized diagnosis and clinical decision support systems.…”
mentioning
confidence: 99%
“…The prognostic features are usually determined using Cox proportional hazard model (CPH) [4]. In the past decade, several radiomics features have shown prognostic value in different diseases especially different types of cancer [5][6][7][8][9]. However, the high dimensionality nature of radiomics features makes the feature selection prone to multiple testing, leading to false positives and low performance in the validation cohorts.…”
Section: Introductionmentioning
confidence: 99%